2018
DOI: 10.1002/cam4.1721
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of long noncoding RNA interactions reveals the potential role in progression of human papillary thyroid cancer

Abstract: Recent scientific evidence has suggested that long noncoding RNAs (lncRNAs) play an important part in tumorigenesis as an important member of competing endogenous RNAs (ceRNAs). Hundreds of RNA sequence data and relevant clinic information are freely accessible in The Cancer Genome Atlas (TCGA) datasets. However, the role of cancer‐related lncRNAs in papillary thyroid cancer (PTC) is not fully understood yet. In this study, we identified 461 RNA sequencing data from TCGA. Subsequently, 45 lncRNAs, 21 miRNAs, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 69 publications
(128 reference statements)
1
19
0
Order By: Relevance
“…We next investigated the underlying molecular mechanisms regulating these processes. LncRNAs have been reported to promote tumor progression through various types of gene regulatory mechanisms, such as epigenetic and transcriptional regulation and serving as ceRNAs for miRNAs [10, 11, 14, 15, 1820]. Therefore, we constructed a ceRNA regulatory network to reveal the unknown mechanisms driving HCC development.…”
Section: Resultsmentioning
confidence: 99%
“…We next investigated the underlying molecular mechanisms regulating these processes. LncRNAs have been reported to promote tumor progression through various types of gene regulatory mechanisms, such as epigenetic and transcriptional regulation and serving as ceRNAs for miRNAs [10, 11, 14, 15, 1820]. Therefore, we constructed a ceRNA regulatory network to reveal the unknown mechanisms driving HCC development.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, microRNAs (miRNAs) are defined as small, noncoding RNAs, which are approximately 21 nucleotides long and are able to repress translation or degradation of mRNA . Accumulating evidences have proved that lncRNAs and miRNAs were abnormally expressed in PTC and can be used to determine the outcomes of PTC patients . Recent studies reported that lncRNA LINC00311 participates in the process of cell proliferation and differentiation .…”
Section: Introductionmentioning
confidence: 99%
“…There were some studies involving the ceRNA network of PTC (You et al, 2018;Zhao et al, 2018;Xu et al, 2019). However, only the global ceRNA network based on the differentially expressed lncRNAs, mRNAs, and miRNAs was constructed in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have revealed that several lncRNAs were associated with the initiation and progression of PTC ( Ding et al, 2018 ; Xia et al, 2018 ; Zhuang et al, 2019 ). The ceRNA network has also been investigated in the study about the roles of lncRNAs in the diagnosis and overall survival of PTC ( You et al, 2018 ; Zhao et al, 2018 ). However, the role of ceRNA network and the prognostic value of lncRNAs, miRNAs, and messenger RNAs (mRNAs) in PTC progression have not been fully explored yet.…”
Section: Introductionmentioning
confidence: 99%